The Correlation of AI Text-to-Speech and Indonesian EFL Students’ Confidence in Pronouncing English Words - Marelia, Febi; Putra, Reko Hary (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores how AI TTS relates to students’ confidence in English pronunciation among English as a Foreign Language (EFL) learners in Indonesia. Previous studies examined TTS perception and pronunciation quality, but none linked AI-TTS use with learners’ confidence, especially in Indonesia. This research used a quantitative correlational design and involved 38 students from an English language education program. Data were collected using a questionnaire measure of AI TTS use and pronunciation confidence. The results indicate that students have positive perceptions of AI TTS and its role in supporting pronunciation confidence. The two variables have a positive and statistically significant correlation, according to Pearson's Product-Moment correlation Test (r = 0.850, p 0.05). Put differently, students with increased interaction with AI TTS tend to feel greater comfortable pronouncing English words. These results also imply that AI TTS can assist the growth of self-confidence, promote autonomous learning, and lessen fear.